2005
DOI: 10.1111/j.1532-950x.2005.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Biomechanical Comparison of the Breaking Strength and Stiffness of Polydioxanone (Sizes 2, 7) and Polyglactin 910 (Sizes 3, 6) in the Equine Linea Alba

Abstract: Given its high initial breaking strength and its relatively longer in vivo strength retention, 7 PD seems an appropriate choice of suture material for closure of the equine linea alba when maximal short-term failure strength is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 13 publications
3
55
0
Order By: Relevance
“…Several models have been used to test the strength of closures of the equine linea alba . The intact cadaver model used in this study was originally described by Magee et al Although it is impossible to simulate in vivo conditions in an ex vivo model, we chose this model because it allows application of 3‐dimensional forces to the incision, whereas in vitro models test only an isolated section of linea alba.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have been used to test the strength of closures of the equine linea alba . The intact cadaver model used in this study was originally described by Magee et al Although it is impossible to simulate in vivo conditions in an ex vivo model, we chose this model because it allows application of 3‐dimensional forces to the incision, whereas in vitro models test only an isolated section of linea alba.…”
Section: Discussionmentioning
confidence: 99%
“…In ex vivo studies, closures performed with polyglactin 910 in a simple continuous suture pattern fail mainly at the surgeon's knot . According to in vitro tests, tied large gauge suture loops break at or adjacent to the knot 90%‐100% of the time . This mode of failure has been attributed to a deformation of the material's original structure due to the load, creating a stress point between the loop and the first throw of the knot .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, polyester is rarely used to close the linea alba because it is nonabsorbable and has increased risk of suture sinus formation 49 . In a similar single cycle to failure model, #7 polydioxanone had the highest breaking strength (316.8 N), followed by #6 polyglycolic acid (281 N), #3 polyglycolic acid (229 N), and finally #2 polydioxanone (193 N) 50 . In a bursting strength ex vivo model, Anderson et al reported that linea alba incisions closed with #7 polydioxanone had greater mean bursting strength and incision failure occurred at the abdominal wall 51 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of suture tensile strength include a wide variation in suture composition, sample configuration, and rate of tensile load application. Reported loading rates range from 5 to 3000 mm per minute on strands that are straight, looped, knotted, or used for actual tissue closure . In addition, degradation rates have been tested on sutures incubated in a variety of environments, including synthetic and biologic fluids, or implanted in animals …”
Section: Introductionmentioning
confidence: 99%